Study of selected harmonics elimination control technology of multi-level inverter - YE Manyuan; LI Song; LI Bing (Gong-kuang zidonghua, 2014)
In order to analyze nonlinear method of selected harmonics elimination PWM technique of multi-level inverter in-depth, several solution models of iterative algorithm were established, solution characteristics of these models were studied, and deficiency of the traditional numerical algorithm in the selected harmonics elimination solution was analyzed and improved. Taking a seven-level inverter as an example, the calculated results in different wavebands of each iterative algorithm were given, and algorithm parameters and elimination effect were compared. The simulation results confirm that solutions of these algorithms are correct.